Designing the user interface : strategies for effective human-computer interaction - Shneiderman, Ben.; Plaisant, Catherine; Cohen, Maxine; Jacobs, Steven (New Delhi : Dorling Kindersley, 2010)
KEY BENEFIT : Provides a broad survey of designing, implementing, managing, maintaining, training, and refining the user interface of interactive systems. KEY TOPICS : Usability of Interactive systems; Guidelines, Principles, and Theories; Managing Design Processes; Evaluating Interface Designs; Direct Manipulation and Virtual Environments; Menu Selection, Form Fills, and Dialog Boxes; Command and Natural Languages; Interaction Devices; Collaboration; Quality of Service; Balancing Function and Fashion; User Documentation and Online Help; Information Search; Information Visualization; Societal and Individual Impact of User Interfaces. MARKET : An ideal reference for HCI professionals.